2020
DOI: 10.21037/jtd-20-3453
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of differentially expressed genes in tumor and paracancerous tissues of patients with lung adenocarcinoma

Abstract: Background: Lung adenocarcinoma is the main pathological type of non-small cell lung cancer (NSCLC).In this study, we analyzed the gene expression profile of lung adenocarcinoma tumor and paracancerous tissues by bioinformatics to assess the genes and signal pathways related to lung adenocarcinoma. Methods: The expression data of GSE7670, GSE27262, and GSE32863 were downloaded from the Gene Expression Omnibus (GEO) database. The three microarray data sets were integrated to obtain common differential expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Our study provides novel insights into the role of Claudin5 in ESCC. We found that Claudin5 expression is suppressed in ESCC tumors, consistent with previous findings in other cancer types such as lung cancer [ 21 , 22 ], breast cancer [ 23 ], and colon cancer [ 24 ]. Moreover, our functional experiments revealed the specific effects of Claudin5 on cells proliferation, migration, invasion, and radiosensitivity in ESCC.…”
Section: Discussionsupporting
confidence: 91%
“…Our study provides novel insights into the role of Claudin5 in ESCC. We found that Claudin5 expression is suppressed in ESCC tumors, consistent with previous findings in other cancer types such as lung cancer [ 21 , 22 ], breast cancer [ 23 ], and colon cancer [ 24 ]. Moreover, our functional experiments revealed the specific effects of Claudin5 on cells proliferation, migration, invasion, and radiosensitivity in ESCC.…”
Section: Discussionsupporting
confidence: 91%
“…However, to date, there is a lack of systematic studies on miR-126-5p and miR-218-5p expression levels in LUAD and their mechanisms of action. Collagen type I alpha 1 chain (COL1A1) is confirmed to be an extracellular matrix protein that is overexpressed in many types of malignant tumors, including lung, breast, and colorectal tumors [ 18 20 ]. In addition, differential expression of COL1A1 predicts poor clinical outcomes (e.g., lymph node metastasis) in lung squamous cell carcinoma patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly used to process and analyze biological data via mathematical formulas and statistical methods[ 24 ]. Numerous studies have investigated biomarkers related to LUAD[ 25 , 26 ], but research conducted thus far has not identified effective biomarkers. It is therefore crucial to analyze LUAD from various aspects, identify the best target molecules for its treatment, and elucidate the biological pathways underlying its development and progression.…”
Section: Discussionmentioning
confidence: 99%